Botulinum Toxin Injection for the Treatment of Upper Esophageal Sphincter Dysfunction. (February 2013) - Kelly, Elizabeth A.; Koszewski, Ian J.; Jaradeh, Safwan S.; Merati, Albert L.; Blumin, Joel H.; Bock, Jonathan M.
Objectives: We sought to review the dysphagia-related outcomes and quality of life in a series of patients with upper esophageal sphincter (UES) dysfunction treated with cricopharyngeal (CP) botulinum toxin (BTX) injection, and to identify patient characteristics or CP muscle histologic features that predict efficacy of BTX injection. Methods: A retrospective chart review was performed on patients with UES dysfunction who underwent CP BTX injection. Dysphagia-related quality-of-life questionnaires based on the Eating Assessment Tool (EAT-10) were mailed to patients. Results: Forty-nine patients (30 female, 19 male; average age, 59 ± 16 years) with UES dysfunction have been treated at our institution with CP BTX injection since 2000. Seventeen of these patients also underwent CP myotomy. Injections of BTX were occasionally repeated after the treatment effect subsided, and the BTX dose varied widely (average, 39 ± 19 units). Improvement in symptoms was noted by 65% of patients. The overall complication rate was minimal, although many patients complained of transient worsening of dysphagia after CP BTX injection. Biopsy specimens of the CP muscle were evaluated in the subset of patients with CP BTX injection who proceeded to myotomy, with results of neuropathic, myopathic, and mixed histologic subtypes. The EAT-10 scores demonstrated a general trend toward improved swallowing outcomes after CP BTX injection. Conclusions: This study reviewed findings from the largest published series of BTX treatment of UES dysfunction and evaluated the efficacy, patient satisfaction, and complications of this procedure. Dysphagia-related quality-of-life outcomes appear to be improved after CP BTX injection.